2011
DOI: 10.7202/045826ar
|View full text |Cite
|
Sign up to set email alerts
|

Élimination des polluants organiques des effluents de l’industrie oléicole par combinaison d’un filtre à sable et un lit planté

Abstract: L’objectif de la présente étude consiste, d’une part, tester les performances d’un filtre à sable pour diminuer la charge organique des margines diluées à 50 % avec des eaux usées urbaines et, d’autre part, compléter le traitement par l’utilisation d’un mélange de plantes aquatiques composé de Phragmites australis, Typha latifolia et Arundo donax sous un régime d’écoulement vertical.Le pilote expérimental est composé d’un filtre à sable suivi d’un système planté. Le filtre à sable est rempli sur une épaisseur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 44 publications
2
9
0
1
Order By: Relevance
“…However, the EC of the B R unplanted filter decreases in relation to the raw effluent concentration. Results are similar to that of Tanner CC, et al [27] cited by Achack M, et al [23], which observed the reduction in EC of the effluent treated in a gravel bed planted with Schoenoplectus validus when the residence time increases. The weekly alternation of supplying and resting times of the filters ensured the aeration of the unsaturated area and the mineralization of the filters.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the EC of the B R unplanted filter decreases in relation to the raw effluent concentration. Results are similar to that of Tanner CC, et al [27] cited by Achack M, et al [23], which observed the reduction in EC of the effluent treated in a gravel bed planted with Schoenoplectus validus when the residence time increases. The weekly alternation of supplying and resting times of the filters ensured the aeration of the unsaturated area and the mineralization of the filters.…”
Section: Discussionsupporting
confidence: 90%
“…These may eventually change the volume of effluent in the filtration system. Considering this change in volume, treatment outcomes could improve, and therefore can be calculated with the actual (or absolute) removal of the filter [18,23]:…”
Section: Real Removalmentioning
confidence: 99%
“…During the process of olive oil extraction different by-product are produced such as olive pomace and OMWW. OMWW is produced in considerable volumes during the process of olive oil extraction: over 30 million m 3 per year (Niaounakis and Halvadakis 2006). OMWW characteristics and composition could change depending on the multiple factors such as origin, maturity of the fruit and extraction method (Ben Sassi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Several purification systems of these effluents were tested, notably in the Mediterranean producer of olive oil basin. Treatment methods are numerous and can be classified into three categories: physical (Achak et al, 2009(Achak et al, , 2011Ouabou et al, 2014), chemical (El Hajjouji, 2007Sifoun, 2008) and biological (Aissam, 2003;Achak et al, 2009Achak et al, , 2011Lakhtar, 2009;Yaakoubi et al, 2009).…”
mentioning
confidence: 99%